Parents’ Roles in Preventing Drug Abuses among Teenagers (A Case Study in Banda Aceh) - M. Nur, Chairan (Jurnal Ilmiah Peuradeun, 2017)
Drug abuse has became a serious problem and related to many aspects of human beings physically, psychologically, socially, etc. It is also leaded to early death, physical disability, social lost, economic impact, etc. Therefore, it is highly recommended appropriated approaches in preventing drug abuse. One basic purpose of this research was to find out the parents’ roles in preventing drug abuse among teenagers. That parent is obligated to educate their children as a main responsibility to God by having the children. Children are educated regularly in any occasions and conditions. The research applied the qualitative approach where the data collection was interview. The research location was in Banda Aceh. In addition, the samples of the study were unemployed and employed parents. The results of the research describes the efforts of parents in preventing their children from abusing drug, parents’ role as supervisors, indeed, parents should know their children friends, solving family problems, collaborating with educational institutions (schools or universities), collaborating with home environment, morever, it could be understood that to stop drug abuse need all parties involvement. Ideally, it should be started from the family. It is believed family is the first “school” for children. The role of parents however is very important in preventing drug abuse as a role model, a guider, a supervisor, in addition, parents need to know their children friends, to solve family problems, to collaborate with educational institutions (schools or universities),and to collaborate with environment nearby the home.